2019
DOI: 10.1007/s10989-019-09838-y
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of Domain 1 of HCV-Core Protein: Iran

Abstract: Hepatitis C virus (HCV) infection is a serious global health problem and a cause of chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma (HCC). Bioinformatics software has been an effective tool to study the HCV genome as well as core domains. Our research was based on employing several bioinformatics software applications to find important mutations in domain 1 of core protein in Iranian HCV infected samples from 2006 to 2017, and an investigation of general properties, B-cell and T-cell epitopes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…HBV and HCV are associated with severe liver disease including chronic active hepatitis, cirrhosis, and hepatocellular carcinoma. [1][2][3][4] Evidence has shown that liver disease caused by hepatitis viruses can be more aggressive and severe in HIV carriers. 5 Globally, more than 71 million people globally have chronic hepatitis C infection, who are at a risk of developing liver cirrhosis and liver cancer, and causes 399,000 deaths every year.…”
Section: Introductionmentioning
confidence: 99%
“…HBV and HCV are associated with severe liver disease including chronic active hepatitis, cirrhosis, and hepatocellular carcinoma. [1][2][3][4] Evidence has shown that liver disease caused by hepatitis viruses can be more aggressive and severe in HIV carriers. 5 Globally, more than 71 million people globally have chronic hepatitis C infection, who are at a risk of developing liver cirrhosis and liver cancer, and causes 399,000 deaths every year.…”
Section: Introductionmentioning
confidence: 99%
“…We have chosen peptides which we have shown to be well recognized in mice, but of different strain (C57Bl/6) [ 49 ]. Inclusion into the assessment of additional peptides (see, for example [ 50 ], IEDB Database) could have resulted in stronger correlations. Recombinant HCV core, which could have provided an opportunity to present all possible epitopes, was be used due to its immunosuppressive effect on the immune cells, also in in vitro tests [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Worldwide, the spread HBV and HCV increase at an alarming rate, this lead to a dramatic impact upon some countries such as Iraq. Also hepatitis B and C viruses are responsible for causing about 80% of liver cancer cases worldwide, and it could be the major cause of morbidity and mortality (Dehghani et al, 2019). In Iraq there is no protocol for blood banking, we followed Word Health Organization recommendations that all donates should be screened for these viruses (HBV, HCV, HIV, Syphilis), because these viruses have greater risk for percipients (WHO., 2017).…”
Section: Discussionmentioning
confidence: 99%